A code for clinical trials centralized monitoring, sharing open-science solutions to high-quality data. - André Daher; Júlio Castro-Alves; Leandro Amparo; Natalia Pacheco de Moraes; Thaís Regina Araújo Dos Santos; Karla Regina Gram Dos Santos; Cristiane Siqueira do Valle; Maria Hermoso; Margareth Catoia Varela; Rodrigo Correa Oliveira (PLoS ONE, 2023)
Monitoring of clinical trials is critical to the protection of human subjects and the conduct of high-quality research. Even though the adoption of risk-based monitoring (RBM) has been suggested for many years, the RBM approach has been less widespread than expected. Centralized monitoring is one of the RMB pillars, together with remote-site monitoring visits, reduced Source Data Verification (SDV) and Source Document Reviews (SDR). The COVID-19 pandemic promoted disruptions in the conduction of clinical trials, as on-site monitoring visits were adjourned. In this context, the transition to RBM by all actors involved in clinical trials has been encouraged. In order to ensure the highest quality of data within a COVID-19 clinical trial, a centralized monitoring tool alongside Case Report Forms (CRFs) and synchronous automated routines were developed at the clinical research platform, Fiocruz, Brazilian Ministry of Health. This paper describes how these tools were developed, their features, advantages, and limitations. The software codes, and the CRFs are available at the Fiocruz Data Repository for Research-Arca Dados, reaffirming Fiocruz's commitment to Open Science practices.